Influence of gentle dryingmethods on the changing of the nutritional characteristics of ramson (Allium ursinum L.) - Friedrich-Ivanics , Judit; Albert, Krisztina Zita; Bánlaki-Doma , Eszter (ÉLELMISZER, TUDOMÁNY, TECHNOLÓGIA, 2022)
The growing popularity of Allium ursinum L. has brought to the fore the possibility of using its seasonal nature as a year-round product, taking advantage of its flavouring and health-promoting properties at any time of the year. In order to increase the shelf-life and to preserve the biological values of ramson, three different gentle drying methods were used in the experiment: lyophilisation, vacuum drying and microwave-vacuum drying, respectively. The drying methods used were applied to both leaves and stalk parts, and the effect of different drying temperatures (40 and 50 °C) was investigated. The dried products were instrumentally and also organoleptically graded. Taking into account the values of water activity, structure, rehydratability, antioxidant capacity and polyphenol content, the samples lyophilised at 50 °C were found to be the most suitable for the production of dried product. When the results of the sensory evaluation were examined, the best results in terms of general aspect were obtained for the vacuum dried and microwave vacuum dried ramson leaves at 50 °C. In case of stalk, green colour was retained most by vacuum-dried samples and faded by lyophilized samples.
Keywords: shallot; Allium ursinum L.; drying method; contents